Chapitre 8. Injustices épistémiques, production et circulation de savoirs inclusifs - Fricker, Miranda; Bujold, Audrey; Vallée-Ouimet, Sandrine (Philosophies et sciences infirmières : contributions essentielles à la discipline, 2024)
Cet ouvrage pédagogique regroupe 18 chapitres écrits par des auteurs en sciences infirmières issus de champs d’expertise variés et des plus pertinents. Chaque chapitre présente les fondements ontologiques et épistémologiques de même que l’articulation des concepts clés de philosophes qui exercent une influence majeure sur les sciences infirmières et la pratique des soins infirmiers à l’aide d’exemples pour la pratique, la recherche et la théorisation dans cette discipline.
Keywords: 2000 à aujourd'hui; 2020-2029; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; phi4336; philosophie; premier cycle; production des savoirs; pédagogie; périodes historiques; québec; régions géographiques; santé; sciences humaines; thématiques; travail; épistémologie

Byproductive labor: A feminist theory of affective labor beyond the productive-reproductive distinction - Whitney, Shiloh (Philosophy and Social Criticism, 2018)
My aim in this paper is to introduce a theory of affective labor as byproductive, a concept I develop through analysis of the phenomenology of various affective labor practices in dialog with feminist scholarship, both on gendered and racialized labor, and on affect and emotion. I motivate my theory in the context of literature on affective and emotional labor in philosophy and the social sciences, engaging the post-Marxist literature on affective and immaterial labor and emphasizing feminist critiques. I argue that affective labor is not only the work of producing affects for others to consume or the reproductive work that rejuvenates and sustains labor power and social life, but also the work of metabolizing waste affects and affective byproducts. Thus, byproductive labor is a neologism I develop to bring into view an affective economy and indeed a political economy of affects to the side of the distinction between productive and reproductive labor in its paid and unpaid variants. I make three central claims: (1) affective labor invariably creates byproducts in the embodied subjectivity of the worker; (2) the unique kind of affective expenditure I call “byproductive” (metabolizing affective surplus, containing affective waste, and producing depleted affective agency) is a defining feature of affective labor not circumscribed by the productive-reproductive distinction; and (3) the marginalized forms of subjectivity and depleted agency constituted through the intersections of this labor with hierarchies of gender, race, and migrant status or global class are themselves byproducts of affective labor. Thus, theorizing affective labor as byproductive captures the uniqueness of affective labor and the forms of exploitation unique to it, but also explains the interaction of affective labor with forms of power that operate through subjection and marginalization. © The Author(s) 2018.
Keywords: amériques; discipline; histoire et politique; philosophie; projet charge mentale; régions géographiques; sciences humaines; thématiques; travail; travail affectif; travail émotionnel; états-unis

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Traite, prostitution, inégalité - MacKinnon, Catharine A. (M éditeur, 2014)
De nos jours, il n'y a pas plus de prise de position favorable à la traite des êtres humains à des fins d'exploitation sexuelle qu'il y a de prise de position publique pour l'esclavage. Il est également très difficile de trouver des partisanes déclarées de l'inégalité… Ce n'est pourtant pas le cas de la prostitution. Certaines personnes sont pour la prostitution. Plus nombreuses sont celles qui considèrent politiquement correct de la tolérer. La plupart présument que, même si elle n'est pas réellement souhaitable, la prostitution est nécessaire, inévitable et sans dommage. Est-ce que la décriminalisation du proxénétisme et la légalisation des maisons closes assureront une plus grande sécurité physique aux personnes prostituées ? Contrairement à la Cour suprême du Canada, la juriste de réputation mondiale, Catharine A. Mac- Kinnon, répond négativement à cette question. Elle soutient que « loin de rendre la vie des prostituées plus sûre, la décriminalisation totale de la prostitution peut même la rendre encore plus dangereuse ». Pour cela, elle s'appuie sur les expériences des pays qui ont légalisé la prostitution et le proxénétisme et sur celles des pays, de plus en plus nombreux, qui décriminalisent les personnes prostituées et pénalisent les clients-prostitueurs ; la stigmatisation liée à l'activité Prostitutionnelle se retourne désormais contre ceux qui en profitent : les prostitueurs et les proxénètes.
Section: 123 pages ; 18 cm.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; inégalités; justice sociale; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution; violences

Cross-dressing to backbeats: An exploration of the practices, wo/men producers, and history of electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.
https://spectrum.library.concordia.ca/id/eprint/977861/1/Madden_PhD_F2013.pdf
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; approches et analyses; communication; discipline; femmes* artistes; genre; historiographie; montréal; musique; mémoires/thèses; philosophie; point de vue situé; périodes historiques; recherche-création; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Pascale Molinier, Le travail du care - Volery, Ingrid (La nouvelle revue du travail, 2013)
Paru aux Éditions La Dispute en 2013, le dernier ouvrage de Pascale Molinier s’attelle à ouvrir la boite noire du care, tel qu’il se déploie dans le quotidien d’un EHPAD de la région parisienne (renommé Villa Plénitude). S’inscrivant dans la lignée des travaux de psychologie et de philosophie qui en ont tenté une formalisation outre-Atlantique, son principal apport est de donner chair à une notion devenue « tarte-à-la-crème », en l’ancrant dans la réalité de situations professionnelles qui dé...
Keywords: care; discipline; europe; france; philosophie; projet charge mentale; psychologie; régions géographiques; sciences humaines; soins aux personnes âgées; thématiques; travail

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
http://hdl.handle.net/10315/31697
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

Mais oui c'est un travail!: penser le travail du sexe au-delà de la victimisation - Parent, Colette; Bruckert, Chris; Corriveau, Patrice; Nengeh Mensah, Maria; Toupin, Louise (Presses de l'Université du Québec, 2010)
La question du travail du sexe fait toujours, aujourd’hui, l’objet de polémiques où le moralisme et les bons sentiments prévalent sur la discussion ouverte. La traite des femmes pour fins de « prostitution » et leur vulnérabilité physique face à la violence et à l’homicide débouchent souvent sur des demandes de répression accrue, et ce sont les travailleuses du sexe qui font les frais de ces discours prohibitionnistes et moralisateurs. Soucieux de véhiculer auprès d’un large public une vision différente de la « prostitution » dans le respect des travailleuses du sexe et de remettre en question les bases du message néo-abolitionniste qui présente ces dernières essentiellement comme des victimes de souteneurs ou de leur fausse conscience, cinq spécialistes ont entrepris la rédaction collective d’un livre pour démystifier plusieurs préjugés liés au travail du sexe. Sont abordés dans ce livre original les fondements du débat actuel de la « prostitution » comme travail, les différentes réponses des régimes juridiques, la variété de pratiques et d’expertises mises en oeuvre par les femmes elles-mêmes, incluant celles des migrantes illégales, et l’action collective des regroupements qui luttent pour une reconnaissance du travail du sexe. Mais oui c’est un travail ! invite donc à déconstruire certains mythes et stéréotypes, et à étayer la preuve à l’effet qu’il est non seulement possible de défendre la légitimité du travail du sexe tout en luttant contre la violence, mais que cela est nécessaire.
Section: xvii, 137 pages ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; phi2030; philosophie; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution

Qu'est-ce que le care?: souci des autres, sensibilité, responsabilité - Molinier, Pascale; Laugier, Sandra; Paperman, Patricia (Éditions Payot & Rivages, 2009)
"Apporter une réponse concrète aux besoins des autres, telle est, aujourd'hui, la définition du care, ce concept qui ne relève pas, comme on l'a longtemps cru, du seul souci des autres ni d'une préoccupation spécifiquement féminine, mais d'une question politique cruciale recoupant l'expérience quotidienne de la plupart d'entre nous. Première synthèse sur cette notion d'une très grande ampleur après les travaux fondateurs de Carol Gilligan dans les années 1980 puis de Joan Tronto dans les années 1990, ce livre concerne aussi bien le domaine du travail que ceux du genre, de l'éthique et de la santé."
Section: 302 pages ; 17 cm.
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail du care

Dictionnaire critique du féminisme - Hirata, Helena (Presses universitaires de France, 2004)
Avortement et contraception, citoyenneté, division sexuelle du travail et rapports sociaux de sexe, domination, famille, féminité-masculinité-virilité, harcèlement sexuel, histoire (sexuation de l'), maternité, migration, mixité, mondialisation, mouvements féministes, parité , patriarcat (théories du), précarisation sociale, prostitution, sexualité, transmissions intergénérationnelles, syndicats, travail domestique, violences.dictionnaire est de changer la façon commune de penser " : l'ambition de Diderot est reprise avec force par les auteurs de ce parcours historique etcritique duféminisme . Cette volonté éditoriale s'exprime dans le choix typologique des entrées : des concepts nouveaux issus de la théorisation féministe, des champs d'intervention des luttes féministes, des notions transversales d'économie et de sociologie du travail.Dictionnaire théorique et politique, pluriel et engagé, cet ouvrage se veut aussi un texte de conviction et d'explication.
Keywords: 1900-1999; approches et analyses; avortement; corps; cours; cycles supérieurs; dictionnaire critique; discipline; europe; fem1000; fem7000; france; har4600; histoire et politique; interdisciplinarité; justice reproductive; lit2815; lit3220; lit3495; militance; outils; ouvrages de références; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexualité; sociologie; thématiques; travail

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis

Invisible Work - Daniels, Arlene Kaplan (Social Problems, 1987)
Our folk understanding of “work” focuses on those activities you “have to do” to get paid for them. Women's work is correspondingly devalued, for it is either unpaid or limited by the demands of the unpaid work in the home. This understanding also includes a moral force. One should contribute to society by working. This paper shows the restrictiveness of these commonsense understandings and discusses the kinds of work that consequently disappear from view. I focus especially on the work involved in the social construction of daily life and in the maintenance and development of institutions. Finally, I present the rationale for expanding the concept of work to include many activities not previously considered in the folk concept: a keener awareness of the work involved in social constructions serves to dignify the labor and engender respect for the workers who do it.
Keywords: discipline; histoire et politique; philosophie; projet charge mentale; sciences humaines; thématiques; travail; travail invisible